A real-world analysis of characteristics and lipid-lowering therapy use in patients initiating treatment with evolocumab in Sweden. (14th October 2021) - Svensson, M K; James, S; Ravn-Fischer, A; Pantev, E; Sorio-Vilela, F; Villa, G; Cars, T; Gustafsson, S; Hagstrom, E
Abstract: Background/Introduction: Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors reduce low-density lipoprotein cholesterol (LDL-C) levels and the risk of cardiovascular events in patients with atherosclerotic cardiovascular disease (ASCVD) in clinical trials. In January 2019, evolocumab reimbursement recommendation in Sweden was broadened to include patients on maximally tolerated oral lipid-lowering therapy (LLT) and either ASCVD and LDL-C ≥2.5 mmol/L, or familial hypercholesterolemia (FH) with no ASCVD and LDL-C ≥3.0 mmol/L. Purpose: Describe characteristics and LLT use in patients initiating treatment with evolocumab in the context of the 2019 reimbursement recommendation in Sweden. Methods: Cross-sectional, population-based, retrospective, observational study of patients initiating treatment with evolocumab between January 2019 and June 2020. Data were obtained from national healthcare registers and electronic medical records, covering more than half of the Swedish population. Results: Out of 1560 patients included, 41% had LDL-C available ≤3 months prior to treatment initiation with evolocumab. Among those with LDL-C available, 79% had ASCVD and 19% had definite, probable or possible FH with no ASCVD. Mean pre-treatment LDL-C levels were 3.7 and 5.0 mmol/L for patients with ASCVD, and FH with no ASCVD, respectively. Most of the patients, 84.6% and 80.0%, respectively, had been ever treated with both statins and ezetimibe. However, 28.0% and 38.3% of them, respectively, were not on oral LLT at the time of treatment initiation with evolocumab. Patient characteristics and LLT use are presented in Table 1. Conclusions: Patients initiating treatment with evolocumab in Sweden had pre-treatment LDL-C levels far from treatment targets, despite being at very high risk for cardiovascular events. Most of the patients had been treated with both statins and ezetimibe in the past. However, almost a third of them were not using oral LLT at the time of treatment initiation with evolocumab. The conditions in the 2019 evolocumab reimbursement recommendation in Sweden were generally met. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Amgen